ANALISIS KETERLAKSANAAN K3 PADA PEMBELAJARAN PRAKTIK DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITAS SEBELAS MARET - Fasya Sebastian Bah; Yuyun Estriyanto; Valiant Lukad Perdana Sutrisno (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
The knowledge aspect regarding K3 in Mechanical Engineering Education still tends to be low. Lack of understanding of K3 implementation has a negative impact on Vocational Education Students. There are still inhibiting factors / causes that influence the implementation of Occupational Health and Safety (K3). This research is a quantitative descriptive study. In connection with the notion of descriptive research, it is carried out by seeking information related to existing symptoms, clearly explaining the goals to be achieved, planning how to approach them, and collecting various kinds of data as material for making reports. (Iyus Jayusman, 2020) Obtained a knowledge level of 90%. This can be seen from students who know about the theory of K3 knowledge. Obtained implementation of 83%. This can be seen from students who understand the implementation of practical learning in the PTM Lab. UNS. Obtained alertness level of 76%. This can be seen from the students who know that the level of awareness in practical learning in Lab.PTM UNS is very good. So that the risk of accidents occurring at the practice site can be minimized by students. In future studies, it can be tried to examine other variables with the same theme because there are still many variables that can be re-examined.